Morphine ameliorates pentylenetetrazole-induced locomotor pattern in zebrafish embryos; mechanism involving regulation of opioid receptors, suppression of oxidative stress, and inflammation in epileptogenesis - ALTURFAN, EBRU IŞIK; MEGA TİBER, PINAR (My University, 2023)
Zebrafish (Danio rerio) is becoming an increasingly important model in epilepsy research. Pentylenetetrazole (PTZ) is a convulsant agent that induces epileptic seizure-like state in zebrafish and zebrafish embryos and is most commonly used in antiepileptic drug discovery research to evaluate seizure mechanisms. Classical antiepileptic drugs, such as valproic acid (VPA) reduce PTZ-induced epileptiform activities. Opioid system has been suggested to play a role in epileptogenesis. The aim of our study is to determine the effects of morphine in PTZ-induced epilepsy model in zebrafish embryos by evaluating locomotor activity and parameters related to oxidant-antioxidant status, inflammation, and cholinergic system as well as markers of neuronal activity c-fos, bdnf, and opioid receptors. Zebrafish embryos at 72 hpf were exposed to PTZ (20 mM), VPA (1 mM), and Morphine (MOR) (100 mu M). MOR and VPA pretreated groups were treated with either MOR (MOR + PTZ) or VPA (VPA + PTZ) for 20 min before PTZ expoure. Locomotor activity was quantified as total distance moved (mm), average speed (mm/sec) and exploration rate (%) and analyzed using ToxTrac tracking programme. Oxidant-antioxidant system parameters, acetylcholinesterase activity, and sialic acid leves were evaluated using spectrophotometric methods. The expression of c-fos, bdnf, oprm1, and oprd1 were evaluated by RT-PCR. MOR pretreatment ameliorated PTZ-induced locomotor pattern as evidenced by improved average speed, exploration rate and distance traveled. We report the restoration of inflammatory and oxidant-antioxidant system parameters, c-fos, bdnf, and opioid receptor oprm1 as the possible mechanisms involved in the ameliorative effect of MOR against PTZ-induced epileptogenic process in zebrafish embryos.
Keywords: Sağlık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Temel Bilimler; Health Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Natural Sciences; TOKSİKOLOJİ; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); TOXICOLOGY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Toksikoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Sağlık, Toksikoloji ve Mutajenez; Fizik Bilimleri; Toxicology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Health, Toxicology and Mutagenesis; Physical Sciences; Pentylenetetrazole; valproic acid; morphine; oxidant-antioxidant; zebrafish embryos; GLUTATHIONE S-TRANSFERASES; NITRIC-OXIDE; EXPRESSION; RATS; EPILEPSY; BEHAVIOR; HIPPOCAMPUS; INVOLVEMENT; IDENTIFY; SEIZURES